Mobility, Context and Cloud - Gr, Tor-Morten; Hansen, Jarle; Ghinea, Gheorghita (International Journal of Interactive Mobile Technologies (iJIM), 2012)
In this paper we pursue the context-aware paradigm in a distributed mobile environment. Context-awareness plays a significant role in the domain of implicit human computer interaction and we present an intelligent context-aware meeting room application. The distributed mobile application consists of multiple mobile operating system clients, a Google Android based presenter that, through proximity technology, communicates with a server in the meeting room, and a Google Cloud backend server. Over 40 users have evaluated the application. Results show that the context aware meeting room was well received by users who displayed a strong positive bias towards cloud integration and, in particular, automatic meeting-note push. We conclude that our context-aware meeting assistant can provide valuable assistance to end users and that there is promise for such use of heterogeneous mobile context-aware platforms.